(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
In this scientific article, further improvement of the management system, procedures and legal foundations of the Uzbek statehood formed under the state administration of Amir Temur in accordance with the needs of the new historical conditions and their content enrichment is covered based on the sources.